Research data management policies in USA, UK and Australia universities: An online survey - Liu, Guifeng; Zotoo, Isidore Komla; Su, Wencheng (Malaysian Journal of Library and Information Science, 2020)
There has been an increase in demand for research data management (RDM) policies to improve the quality of research data however, there is no clear-cut policy content to guide the process. The purpose of this study is to identify the existing RDM policies. Specifically, the study compares and differentiates the RDM policies in three developed nations (USA, UK and Australia) to ascertain how the policies vary. The RDM policies of 100 universities from the three countries, that are present online were retrieved and content analysis approach using NVivo and SPSS were performed. The results from the analysis revealed that the common underlying facts of the policies were found in the areas of access, retention, sharing, storage and ownership. All the universities share the same core values in the management of their research. They exhibit that Data Management Plan (DMP) is essential. The study concluded that the differences in the data management are mostly issues of focus areas. More so, there is no fixed retention period for research data. To resolve the few differences identified, common criteria for data management is proposed for policy considerations to ensure compliance. Finding from the study is significant to developing countries as it adds to the discourse on data management policies. The study will also enable policy makers in developing countries to draw empirical evidence from the developed world on RDM and this will form a basis for policy direction.